Exploring the impact of professional soccer substitute players on physical and technical performance - Pan, P.; Li, F.; Han, B.; Yuan, B.; Liu, T. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Substitutions are generally used to promote the match performance of the whole team. This study aimed to analyze the performance of substitute players and explore the performance difference among substitute players, completed players, and replaced players across each position.